Criminal Career Dimensions Research: Implications for the Treatment of Chronic Offenders - Bogićević, Dragana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
A criminal career describes long-term patterns of criminal activity in the life-course of an offender. It is characterized by onset, persistence, escalation, and termination. Knowledge of the continuum of a criminal career and its dimensions is a direct prerequisite for understanding the development of criminal behavior, as well as for treating chronic offenders. Numerous research studies on criminal career and its dimensions, especially frequency and duration, make their contribution to the treatment of the so-called chronic offenders. Therefore, the aim of this paper is to show how the existing knowledge can be used in the treatment of chronic offenders by presenting the main research findings on the dimensions of the criminal career. After an explanation of the dimensions of a criminal career, the main findings of research on the dimensions of a criminal career are presented, and finally, the implications that may be relevant for improving the treatment of chronic offenders are presented.